MUSICAL CHALLENGES AS PRECURSOR IN SHAPING MUSICAL IDENTITY: THE CASE OF BIG STAGE SEASON 1 CONTESTANTS - Sissy Imann Mohammad Kamil (Journal of Islamic, Social, Economics and Development, 2023)
Singing competition presents an opportunity for aspiring singers to showcase their talent. In the twenty-first century culture, singing competitions in the setting of reality TV shows have dominated television schedules and were believed to help talents to kick start their singing career. This research focuses on the musical identity formation of a singer through overcoming musical challenges faced during participation in singing musical reality TV show. The research involves participants from local singing competition Big Stage Season 1 due to its unique requirements which limits its participation only from singers who already have some level of presence in the music industry. The framework on musical identity is defined broadly to be the signature vocal quality that people associate a singer with. The primary data collection method was done through semi-structured interviews based on the self-perception of each research participant, while thorough document analysis for each weekly concert was done to look into the vocal style and musical arrangement, feedback from judges, and total marks obtained. Post-competition career growth data was collected as an indicator of the participants current relevance in the industry. Findings from this research indicate that all participants underwent some form of musical identity formation and maturity process throughout the competition. The stages of identity formation however differ between each of them, with some only at the discovery phase while others went through identity self-negotiation. It was discovered that the challenges imposed on the participants pushed them to rethink their musical approach, while giving them opportunities to experiment with different musical identities and concepts. The findings from this research aims to provide an outlook to aspiring singers on the impact of musical challenges in singing reality TV show to the musical identity formation of a singer.